ChemInform Abstract: Saturation Vapor Pressures and Transition Enthalpies of Low‐Volatility Organic Molecules of Atmospheric Relevance: From Dicarboxylic Acids to Complex Mixtures. Issue 28 (July 2015) - Bilde, Merete; Barsanti, Kelley; Booth, Murray; Cappa, Christopher D.; Donahue, Neil M.; Emanuelsson, Eva U.; McFiggans, Gordon; Krieger, Ulrich K.; Marcolli, Claudia; Topping, David; et al.
Abstract Review: 257 refs.